المنهج البنيوي النفسي: التحولات والأبعاد والإشكالات /Psychoanalytic Structuralism Method; Transformation, Dimensions and Problems - ʽAbdullah Al-ʽAnbar, ʽUmar (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2019)
ملخص البحث: تشكل البنيويات نظريات نقدية غربية سيطرت على الساحات النقدية منذُ بدايات القرن التاسع عشر، وقدمت البنيوية النفسية كثيراً الأفكار والأدوات والنماذج والمحاولات المفيدة في معاينة النصوص الأدبية وتحليلها، وتحتاج البنيوية المعاصرة إلى مراجعة شاملة لتحولاتها؛ ولذلك اختار هذا البحث البنيوية النفسية موضوعاً له، واتبع الباحث المنهج الوصفي والتحليلي، وتهدف الدراسة إلى بيان تحولات البنيويات، والبنيوية النفسية، وإشكالات البنيوية النفسية. من نتائج الدراسة ما يأتي: أظهر البحث تطبيق البنيوية النقدية والنفسية جملة من الأدوات القادرة على وعي أبعاد النص الأدبي وتجلياته، وأظهرت الأدوات المنهجية التي يعتمدها المنهج البنيوي النفسي قدرة تحليلية للنصوص الأدبية، وتقوم المناهج النقدية البنيوية وما بعدها على فكرة الدمج والتعديل؛ حيث يتم الدمج بين الجوانب البنيوية والأبعاد النفسية لتخرج لنا البنيوية النفسية مؤلفة منهجاً نقدياً نفسياً جديداً ذا أبعادٍ خاصة ومهمة. الكلمات المفتاحية: تحولات البنيويات-البنيوية النفسية-الأبعاد-العلاقات-الإشكاليات. Abstract Structural approaches are Western theories of literary criticism which prevailed since it first appeared in the 19th century. Psychoanalytic structuralism, discussed in this paper, tends to offer multifarious conceptions, tools, models, and disciplines for scrutinizing and analyzing literary works. Therefore, contemporary structuralism requires a comprehensive review to investigate their transformations. For this reason, psychoanalytic structuralism is the focus of this paper. The researcher uses the analytical descriptive method. The study aims to explain the transformation of structuralisms, psychoanalytic structuralism, and its problems. Among the conclusions of the study are; the application of critical psychoanalytic structuralism has proven the benefit of a number of tools able to bring awareness about the dimensions and manifestations of a literary text. The methodological tools that are used by the psychoanalytical structuralism method have the analytical ability on literary texts. This method is based on the idea of combination and amendment; combining the aspects of structuralism and the psychological dimensions to give us psychoanalytical structuralism as a critical psychological method that has significant and specific dimension. Keywords: Psychoanalytic structuralism, the transformation of structuralisms, psychoanalytic structuralism, problems. Abstrak Pendekatan Strukturalis adalah merupakan teori-teori kirik kesusasteraan yang telah timbul semenjak kurun ke 19. Strukturalisma psikoanaltik yang dibincangkan di dalam kertas ini menawarkan pelbagai konsep, peralatan, acuan dan disiplin untuk mendekati dan menganalisa kerja-kerja kesusasteraan. Oleh kerana itu, struktularisma semasa memerlukan ulasan yang komprehensif untuk disingkap perubahannya. Untuk tujuan ini, strukturalisma psikoanalitik akan diberikan tumpuan di dalam kertas kajian ini. Pengkaji menggunakan metod analitik dan deskriptif untuk menerangkan perubahan strukturalisma, strukturalisma psikoanalitik dan permasalahannya. Di antara rumusan kajian ialah: penggunaan strukturalisma psikoanalitik secara kritikal telah terbukti dapat memberi manfaat kepada beberapa wadah yang dapat memberikan kesedaran tentang dimensi dan manifestasi sesuatu teks sastera itu. Alatan metodologi yang digunakan oleh metod strukturalisma psikoanalitikal mempunyai potensi menganalisa teks kesusasteraan. Metod ini adalah berdasarkan kepada ide penggabungan dan perubahan; yang menggabungkan aspek-aspek strukturalisma dan dimensi psikoanalitik yang memberikan kita strukturalisma psikoanalitik sebagai satu metod psikologikal yang kritikal yang mempunyai kepentingannya dan dimensinya yang tersendiri. Kata kunci: Strukturalisme psikoanalitik, transformasi struktur struktur, struktur struktural psikoanalitik, masalah.